PERAN MODAL SOSIAL DALAM PEMBANGUNAN BERBASIS KEARIFAN LOKAL (Kajian Realitas Sosial di Kecamatan Peukan Bada Kabupaten Aceh Besar) - Vilzati, Vilzati (Universitas Jabal Ghafur, 2024)
The objective of the research is to analyze local wisdom as the social capital of development in the study of social reality in Peukan Bada district of Aceh Besar as well as to analyse the local forms of wisdom used in the construction of Peukan bada districts in Aceh Besar. The research uses a qualitative approach with data collection techniques through observations, interviews and documentation. The investigator's informant determines purposive sampling. The results of the research show that the high level of local wisdom as the social capital of the community of Peukan Bada district of Aceh is due to the strong social base, the presence of the orientation and historical dimensions of the formation of social values and norms as well as the high degree of mutual cooperation in the life of society, thus having an impact on the implementation of development. The local wisdom that members of the community possess as capital in the construction of trusts, social networks and social norms is still strong enough to support the realization of development. Then the form of local wisdom that supports the development of agreement, cooperation, participation became a habit to produce compactness in society, and the spirit to do good in the implementation of development and the strong sense of social solidarity in society.Keywords : Social Capital, Development, Local Wisdom